The Role of the Audit Committee in Moderating the Relationship between Financial Conditions and Profitability with Financial Statement Fraud - Winda Firdiana; Hidayat Darwis (International Journal of Management Science and Information Technology, 2026)
This research investigates the influence of financial distress and profitability on financial statement fraud, while also assessing the role of the audit committee as a moderating factor in companies within the consumer non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Employing a causal approach, the study aims to establish the relationships among the variables involved. A purposive sampling method identified 39 companies after excluding outlier data. The analysis relies on secondary data obtained from the audited annual financial statements of each firm. Panel data regression serves as the analytical method. The findings reveal that financial distress positively correlates with financial statement fraud, whereas profitability does not demonstrate a significant relationship with fraud occurrences. Notably, the audit committee plays a crucial role in mitigating the positive impact of financial distress on fraudulent activities. However, it does not effectively moderate the link between profitability and financial statement fraud. Collectively, financial distress, profitability, and the audit committee exert influence on the prevalence of financial statement fraud.